2020
DOI: 10.1002/jbio.202000221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold atmospheric pressure plasma and disinfecting agents on Candida albicans in root canals of extracted human teeth

Abstract: Reinfection in endodontically treated teeth is linked to the complexity of the root canal system, which is problematic to reach with conventional disinfection methods. As plasma is expected to have the ability to sanitize narrow areas, the aim of this study was to analyze the effect of cold atmospheric pressure plasma (CAP) on Candida albicans in root canals of extracted human teeth. CAP was applied as mono treatment and in combination with standard endodontic disinfectants (sodium hypochlorite, chlorhexidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Kerlikowski et al used an Ar/O 2 jet device to treat C. albicans in root canals. The reduction achieved was 2.1 CFU in less than 600 s [ 65 ]. He/O 2 resulted in total inactivation of a C. albicans and a C. krusei biofilm within 60 s [ 72 ], whereas another group of authors showed a reduction of 0.4 to 0.8 log 10 CFU dependent on the amount of oxygen admixed [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kerlikowski et al used an Ar/O 2 jet device to treat C. albicans in root canals. The reduction achieved was 2.1 CFU in less than 600 s [ 65 ]. He/O 2 resulted in total inactivation of a C. albicans and a C. krusei biofilm within 60 s [ 72 ], whereas another group of authors showed a reduction of 0.4 to 0.8 log 10 CFU dependent on the amount of oxygen admixed [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal effect of CAP on C. albicans was investigated in 14 studies, 13 on plain surfaces, and 1 in an endodontic model [ 65 ]. In accordance with the findings from the bacterial experiments, the reduction increased with in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This single-electrode tiny plasma jet without the major drawbacks of conventional plasma jet (high voltage, high flow rate, reactive species delivery, plasma jet volume, and discharge formation in the organ) will have more potential biomedical applications, especially for in vivo clinical applications. For example, plasma disinfects bacteria in the oral cavity, such as Enterococcus faecalis and Candida albicans [36,37]. This reliable and user-friendly tiny plasma jet could be directed manually to target a root canal for disinfection.…”
Section: Resultsmentioning
confidence: 99%